Newspaper-Style Expressivization and Dialogization Trends (News Block of English-Language Newspapers) - E. A. Nikonova (Научный диалог)
The article is devoted to the analysis of the state of the modern newspaper style. The author notes that the theory of newspaper style was developed in the 60s of the last century and since then has undergone a number of changes that have not received sufficient coverage in linguistics. Attention is paid to the changes in the modern newspaper style, among which one can single out the strengthening of emotionality and dialogue. It is emphasized that these features are generally characteristic of media texts and, correspondingly, newspaper-style texts included in the media space. According to the presented research results, these tendencies are realized in newspaper-style texts through the use of colloquial vocabulary, repetition, quotation and question in the narrative (or rhetorical question), word play. It is shown that, at the same time, the majority of news reports (81 %), which constitute the core of the newspaper style and most clearly reflect its features, retain the key style characteristics: the prevalence of the message function, conciseness, brevity, the desire for emotionless and non-judgmental presentation. It seems that the statements about the “blurring” and disappearance of the newspaper style are premature and are caused by its evolution and dynamics.